2022
DOI: 10.57040/jllls.v2i1.189
|View full text |Cite
|
Sign up to set email alerts
|

A morphosyntactic and semantic analysis of toponyms among the Luhya: A case of Bungoma County

Abstract: Onomastics,the study of names has remained an area of marginal significance in research despite its importance in language studies. This paper  conducts a  morphosyntactic and semantic analysis of toponymns (place names) among the Luhya group of speakers  in Western Kenya, Bungoma County. A structural and  functional approach is used  to analyse the naming  patterns  with the idea that African names, as signs of language, can be divided into two morpho-syntactic categories:nominal that is, they constitute sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 2 publications
1
7
1
Order By: Relevance
“…In example 19 above, mwana ũcio-rĩ, anyitĩte gĩkombe-rĩ, nĩakũngũĩire ũhotani ũcio (that child, holding the trophy, celebrated that victory), the domain is mwana ũcio (that child), which is echoed by prefix a-the concordial class marker, in the verb anyitĩte (holding). Prefixes have been found to be a significant feature in morphosyntax of Luhyia, also a Kenyan Bantu language, in changing common nouns into names of places (Mandillah, 2022). The elaboration strategies identified in hypotactic Gĩkũyũ clause complexes are summarised in Table 3 below:…”
Section: Non-finite Clause Elaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…In example 19 above, mwana ũcio-rĩ, anyitĩte gĩkombe-rĩ, nĩakũngũĩire ũhotani ũcio (that child, holding the trophy, celebrated that victory), the domain is mwana ũcio (that child), which is echoed by prefix a-the concordial class marker, in the verb anyitĩte (holding). Prefixes have been found to be a significant feature in morphosyntax of Luhyia, also a Kenyan Bantu language, in changing common nouns into names of places (Mandillah, 2022). The elaboration strategies identified in hypotactic Gĩkũyũ clause complexes are summarised in Table 3 below:…”
Section: Non-finite Clause Elaborationmentioning
confidence: 99%
“…The language is predominantly spoken in the central region of the country but has spread to other areas (Gichohi & Subiyanto, 2022). Mandillah (2022) stresses the importance of studying native languages, noting that, for instance, they unite the native speakers and also bear the values of the speakers. Based on Halliday and Matthiessen (2014) Functional Grammar Theory, this article sought to examine clause complexing in Gĩkũyũ, specifically focusing on how the joined clauses are related.…”
mentioning
confidence: 99%
“…It is intended so that people can acquire necessary information regarding the areas they visit so that immigrant communities can know an area's history, traditions, customs, rules, and geography. (Sari, 2022;Triana et al, 2022;Kumala et al, 2022;Halfian et al, 2022, & Nugraha, 2023 Using a different approach, Mandillah (2022) accepts that the name of an area is affiliated with the morphosyntactic structure of a language, so Mandillah researched named areas in the West Kenya region, Bungoma County. It was revealed that their toponyms were assembled based on history, topographical features, and climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The results reveal that most PNs are descriptive of where they belong in whole or part. Anindo (2016) and Mandillah (2022) studied PNs in Kenya. Anindo (2016) studied the meanings and morphology of Lulogooli PNs.…”
mentioning
confidence: 99%
“…The study also indicates that Lulogooli PNs, generally, have referential meanings and are derived from prominent persons, unique deaths, water sources, pioneers or clans, local insects, plants or trees, local terrain, and description of characteristics of a place. Mandillah (2022) examined the morphosyntax and semantics of Luhya PNs through a structural and functional approach. The results show that Luhya PNs are formed via grammatical rules that emanate from word transformations.…”
mentioning
confidence: 99%